Pengaruh Implementasi Program Sekolah Pasar Modal, Motivasi Investasi, Dan Efikasi Keuangan Terhadap Minat Berinvestasi Di Pasar Modal (Studi Kasus pada Mahasiswa FEB UNISMA) - Lestari, Ani; Malikah, Anik; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Investment interest among students has been increasing along with the rise in financial literacy and access to capital market education. This study aims to analyze the influence of the Capital Market School Program implementation, investment motivation, and financial efficacy on students' interest in investing in the capital market. The research was conducted among students of the Faculty of Economics and Business, Islamic University of Malang (FEB UNISMA). A quantitative research method with a descriptive approach was employed. Data were collected through questionnaires distributed to 253 FEB UNISMA students from the 2021 cohort who had taken investment-related courses. The data were analyzed using multiple linear regression. The findings indicate that the implementation of the Capital Market School Program has a significant and positive effect on students’ investment interest. Investment motivation also significantly influences students' engagement in investment activities, where highly motivated students are more inclined to invest. Additionally, financial efficacy contributes positively to investment interest, meaning that the higher a student’s confidence in managing finances, the greater their interest in investing. This study highlights the importance of capital market education in fostering investment interest among students and the need for institutional support in enhancing financial literacy. Keywords: Investment interest, Capital Market School, Investment Motivation, Financial Efficacy, Capital Market.